Fatigue Delamination Crack Growth in GFRP Composite Laminates: Mathematical Modelling and FE Simulation - Hassan Ijaz; Waqas Saleem; Muhammad Zain-ul-abdein; Aqeel Ahmad Taimoor; Abdullah Salmeen Bin Mahfouz (International Journal of Aerospace Engineering)
Glass fibre-reinforced plastic (GFRP) composite laminates are used in many industries due to their excellent mechanical and thermal properties. However, these materials are prone to the initiation and propagation of delamination crack growth between different plies forming the laminate. The crack propagation may ultimately result in the failure of GFRP laminates as structural parts. In this research, a comprehensive mathematical model is presented to study the delamination crack growth in GFRP composite laminates under fatigue loading. A classical static damage model proposed by Allix and Ladevèze is modified as a fatigue damage model. Subsequently, the model is implemented in commercial finite element software via UMAT subroutine. The results obtained by the finite element simulations verify the experimental findings of Kenane and Benzeggagh for the fatigue crack growth in GFRP composite laminates.